Analisis Kekuatan Tarik dan Ketangguhan Sambungan Las Busur Rendam Baja Karbon Rendah dengan Variasi Kandungan Mn. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The research aims to investigate the strength and toughness of submerged arc steel weld metals with various manganese contents. A series of bead on plate welds were made on 22 mm thick SM 490. The welding process was performed on flat position with current of 450 A, voltage DC of 30 V and travelling speed of 6 mm/s which is equivalent to heat input of 2 IGI/mm. Fillers used were EL12, EM12K and EH12K with diameter 4 mm. Flux basicity index (BI) of 1.6 (semi basic). Results of this investigation show that the weld metal with 1.537%wt Mn has the highest tensile strength with value of 625 MPa, weld metal with 1.369%wtMn has the highest toughness at room temperature, whereas at temperature -40 Â°C weld metal with 1.537%wtMn has the highest toughness.